"A Decade in Leaps and Bounds": Pharmacy in Jordan- revisited - Abu Asab, Mohammad; Abushams, Leen; Albsoul, Abla; Wazaify, Mayyada (Jordan Journal of Pharmaceutical Sciences, 2019)
This paper comes after 10 years of the previous “Pharmacy in Jordan” review that was published in American Journal of Health System Pharmacy in 2005. The aim of this new article is to highlight the most important achievements that have been made in different sectors of Pharmacy in the Hashemite Kingdom of Jordan. This leap involved pharmaceutical industry, education, clinical pharmacy practice, technology and pharmacy others. Technology is now used on a wider scale in governmental health sectors and HAKEEM program is a living example. Many pharmacies currently specially chain pharmacies, utilize various forms of pharmacy management systems with bar-code reading to control point of sales (PoS), inventory and customer relationships. Most chain pharmacies now also keep electronic patient medication records or use software to keep patient prescription data and check drug interactions. Furthermore, chain pharmacies have expanded from just one in 2001 to a total of 56 chains in 2017, with the first drive-through pharmacy in Jordan launched in the same year. The role of the pharmacist in Jordan has shifted gradually, with approximately 24 hospitals out of 106 total hospitals in the country having some established form of clinical pharmacy services.